Sistem Informasi Invoice Huff & Puff Unit And Cyclic - Hilda Herasmus (Journal Of Science Education And Management Business, 2023)
Maintenance operations of oil wells in the company of PT. CPI using Cyclic Steam Generators and facilities will increase oil production, For each of the job’s result that has been completed according to the agreement between the contractor (PT UIRB) with the user (PT CPI), the monthly billing will be done by the contractor with attaching the data results of the job or daily report. The web-based system existence, The time will be faster reporting process which reports the results of the job that has been completed will be saved into the database and then processed into a monthly report and invoice, then the billing process will be faster and any required reports will be presented easily. Every labor leaders in each area will be on time in the job reports by the facility head of the company's website and makes it easy to see the job every day